Analysis Of Mangrove Land Cover In The Sawo Marine Conservation Area, North Nias District - Ifanda, Dayun; Slamet, Bejo; Yunasfi, Yunasfi; Sri Hastuti, Liana Dwi (Tunas Geografi, 2024)
Sawo sub-district of North Nias Regency has a mangrove ecosystem that has been designated as a Regional Marine Conservation Area (KKLD) with an area of 29,230.85 ha. The 2005 earthquake and tsunami are reported to have caused damage to mangrove ecosystems due to rising land levels. The increase in land surface has resulted in the destruction of mangroves in this area. This impacts the sustainability of the mangrove ecosystem in this region and is important to study. This study aims to analyze changes in mangrove land cover after the tsunami in 2006 to 2022 and to analyze the impact of changes in mangrove land cover. The results found that mangrove land cover continues to experience a reduction in area; in 2006, an area of 139.78 ha continued to decline until the remaining 70.87 ha in 2022. This is due to the increasing population growth that causes mangrove forest degradation and land conversion into agricultural land, plantations, and infrastructure. The increase in population is a driving force, land clearing for settlements and plantations is a pressure factor (Pressures), land use change is a factor of existing conditions (State), and reduced mangrove land area is part of the impact (Impact). Coastal spatial planning and counseling to reforestation is a response (Response). Land conversion to other uses contributes to this area's continued loss of mangrove land.Keywords: Mangrove; Land Cover; GIS; DPSIR